Approach to the patient with a palpable breast mass. Issue 10 (October 2022) - Jackson, Toni; Carmichael, Caroline; Lovett, Katie; Scott, Morgan; Shakya, Sabrina; Sotak, Megan
ABSTRACT: Breast mass is a common finding in patients presenting to primary care, women's health, or urgent care clinics. There are multiple etiologies that can cause a palpable breast mass both benign and malignant. PAs must know how to approach a patient with a palpable breast mass as well as what appropriate diagnostic evaluation is needed.